Groundbreakers : celebrating 50 years of female excellence in sports [videorecording (DVD)]. - King, Billie Jean; Osaka, Naomi, 1997-; Joyner-Kersee, Jacqueline, 1962-; Lieberman, Nancy, 1958- (PBS, 2023)
Celebrate 50 years of female excellence in sports through the eyes of athletes who changed the system. Hosted by tennis legend and activist Billie Jean King, the film weaves together stories of eight icons to discuss how their own struggles and achievements shaped women's sports.